LEARNING A FOREIGN LANGUAGE WITH THE HELP OF EDUCATIONAL FILMS - Yakubova , Kamola Shokirovna (Educational Research in Universal Sciences, 2023)
Learning a new language is one of the basic principles that can promote education and build capacity in educational system. Knowing a new language gives big opportunities for learners and teachers to participate in international exchange programs and conferences which will help and alleviate the process of bringing new concepts and prospects back to their countries. However, learning and teaching a foreign language is not easy, so we have some difficulties that we can come across in many cases. Each student has his own problems but the most common that we can notice in students are lack of grammar, vocabulary, hesitation in speaking and incorrect pronunciation.